Measuring online interaction - Ali, Mohd. Fadzli; Joyes, Gordon (Persatuan Teknologi Pendidikan Malaysia, 2007)
Equivalency Theorem (Anderson, 2003) suggests â€œdeep and meaningfulâ€? learning is possible as long as one of the main forms of interaction is at a high level: student-teacher; studentstudent; student-content. In measuring an online interaction, one common technique used is content analysis. It is a technique to study the interaction patterns among students and tutors. It also enables researcher to study human behaviour in an indirect way through an analysis of their communication. (Fraenkel and Wallen, 2006). This paper will look at (1) the use of content analysis used to measure on-line interaction and (2) the application of Salmonâ€™s Five-Step model in analysing online interaction which has been criticised by Mouleâ€™s E-learning Ladder model.